Transforming African Cities: United Nations Technical Assistance, Urban Development, and Modernization in a Decade of Decolonization, c. 1955–1965 - Wolffhardt, Tobias (Comparativ, 2020)
United Nations experts played an important role in formulating policies of urban development in Sub-Saharan Africa during the late 1950s and early 1960s. Even though the process of rapid urbanization in the region had begun in the 1920s, colonial regimes had been slow to react to this challenge. Thus, governments of the newly independent countries were confronted with a number of structural problems, among them the lack of an efficient building materials industry and qualified personnel or the virtual non-existence of data and statistics. In this context, a discourse on strategies to cope with the challenge developed that went far beyond pragmatic approaches and involved more general questions about the interrelationship of urbanization, modernization and development in Sub-Saharan Africa.